Correction: In situ study of strontium segregation in La0.6Sr0.4Co0.2Fe0.8O3−δ in ambient atmospheres using high-temperature environmental scanning electron microscopy. Issue 29 (10th July 2018) - Niania, Mathew; Podor, Renaud; Britton, T. Ben; Li, Cheng; Cooper, Samuel J.; Svetkov, Nikolai; Skinner, Stephen; Kilner, John
Abstract : Correction for ' In situ study of strontium segregation in La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ in ambient atmospheres using high-temperature environmental scanning electron microscopy' by Mathew Niania et al., J. Mater. Chem. A, 2018, DOI: ;10.1039/c8ta01341a .